The Impact of Religiosity on Tax Compliance among Turkish Self-Employed Taxpayers - Benk, Serkan (Religions, 2016)
The aim of this study is to explore the impact between religiosity and voluntary tax compliance and enforced tax compliance for self-employed taxpayers in Turkey, where Islam is the predominant religion. A questionnaire survey was administrated to 375 male and 28 female self-employed taxpayers. In this paper, two dimensions of religiosity, namely interpersonal and intrapersonal religiosity, were studied. Factor analysis and ordinary least squares regression methods were used for data analyses. The results of the study illustrate that general religiosity has a statistically positive impact on both voluntary and enforced tax compliance. When we consider the dimensions of religiosity, only intrapersonal religiosity appears to be a significant contributor only to voluntary tax compliance. Nevertheless, interpersonal religiosity has no significant statistical effect on both voluntary and enforced tax compliance. This is one of the pioneer studies of its kind, and investigates the relationship between religiosity and tax compliance from the perspective of developing countries, particularly, Turkey.